2011
DOI: 10.1074/jbc.m111.253468
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related Transcription Factor AtfB Integrates Secondary Metabolism with Oxidative Stress Response in Aspergilli

Abstract: In filamentous fungi, several lines of experimental evidence indicate that secondary metabolism is triggered by oxidative stress; however, the functional and molecular mechanisms that mediate this association are unclear. The basic leucine zipper (bZIP) transcription factor AtfB, a member of the bZIP/CREB family, helps regulate conidial tolerance to oxidative stress. In this work, we investigated the role of AtfB in the connection between oxidative stress response and secondary metabolism in the filamentous fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
0
17

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(171 citation statements)
references
References 50 publications
8
146
0
17
Order By: Relevance
“…These results were also verified by semiquantitative PCR (data not shown). Analysis of the effect of veA on the expression of atfB, encoding a transcription factor known to bind to the promoter regions of oxidative stress response genes (29,33), was done separately. Our results indicated that veA is also necessary for the increase in the expression of atfB in the presence of hydrogen peroxide over time (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were also verified by semiquantitative PCR (data not shown). Analysis of the effect of veA on the expression of atfB, encoding a transcription factor known to bind to the promoter regions of oxidative stress response genes (29,33), was done separately. Our results indicated that veA is also necessary for the increase in the expression of atfB in the presence of hydrogen peroxide over time (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polyclonal anti-AtfB antibodies (YSR) were used to block formation of DNA-protein complexes (shift inhibition EMSA) as described previously (29). Five micrograms of nuclear protein extracts was incubated in a DNA binding buffer for 15 min at 30°C with 5 l of anti-AtfB antibody (5.5 g/l), or preimmune serum obtained from the same rabbit as the antibody was generated.…”
Section: Methodsmentioning
confidence: 99%
“…bZIP-type transcription factors may regulate secondary metabolite production, either directly by binding at promoters of genes encoding key elements of the biosynthetic machinery, as shown for RsmA and other bZIPs (Roze et al, 2011;Yin et al, 2012), or via modulating intracellular ROS levels through fine-tuning the activity of the antioxidative defence system, as demonstrated for NapA orthologues in A. ochraceus and A. parasiticus (Reverberi et al, 2007(Reverberi et al, , 2008(Reverberi et al, , 2012. This theory has also been supported by observations that the inhibition of oxidation processes including lipid peroxidation hinders biosynthesis of mycotoxins, including aflatoxin (Jayashree & Subramanyam, 1999, 2000, and the addition of lipid peroxidationstimulating agents to fungal cultures increases the yields of certain metabolites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…YES liquid medium (2% yeast extract, 6% sucrose [pH 5.8]) (6) was used as an aflatoxin-inducing rich growth medium, and YEP liquid medium (2% yeast extract, 6% peptone [pH 5.8]) (7) was used as an aflatoxin-noninducing medium. An aliquot of frozen conidiospores from each strain was used to inoculate 100 ml of these growth media (250-ml Erlenmeyer flask carrying 5-or 6-mm glass beads) at 10 4 spores per ml, and these cultures were incubated for 40 h in the dark at 30°C with shaking (150 rpm) as described previously (standard growth conditions) (7).…”
Section: Methodsmentioning
confidence: 99%